Drip irrigation evaluated in Santa Maria Valley strawberries - B Hanson; W Bendixen (California Agriculture, 2004)
About 4,000 acres of strawberries are grown in the Santa Maria Valley using drip irrigation. In order to help growers irrigate more effectively, we conducted studies to determine crop evapotranspiration; irrigation system performance; patterns and levels of soil salinity; soil moisture content around drip lines; and irrigation water quality. We also developed canopy growth curves. Results at 13 sampling locations showed maximum canopy coverage of less than 75%. Crop evapotranspiration ranged from 12.2 inches to 15.6 inches. Irrigation-system evaluations revealed that most of the distribution uniformities were greater than 80%, considered acceptable. The electrical conductivities of the irrigation water ranged from 1 deciSiemens per meter (dS/m) to 2.36 dS/m; levels over 1 dS/m could result in yield reductions in strawberries. However, 79% of the samples had electrical conductivities equal to or less than 1.5 dS/m. Levels of soil salinity in the vicinity of drip lines ranged from 1 dS/m to 3.5 dS/m. This information can help growers calculate crop water needs and estimate irrigation set times.